Consumer attitude toward shopping malls : a study on consumer activities inside shopping malls and consumer shopping orientations - Karumanan, Malathi (2000)
This study aims to identify consumer attitude toward shopping malls, focusing on the activities that consumers engaged in while inside the mall and the different orientations that draw consumers to shopping malls. Literature research revealed that people's attitude toward shopping is a function of many variables, some of which are unrelated to the actual buying of products. Therefore a study on the activities that consumers involve in while inside the mall and the reasons/benefits they patronize shopping malls will provide a better understanding on consumer attitude toward shopping malls. Previous studies highlighted thirty one orientations that attract consumers to shopping malls. These orientations were then grouped into seven categories and together with fourteen items relating to consumer activities and twelve demographic items, formed a six page questionnaire. Hundred and twenty respondents were approached at three shopping malls, namely One-Utama, Mid-Valley Mega Mall and Suria KLCC. The data obtained from them were analyzed using frequency analysis, percentage, mean score and cross tabulation. The findings of the study indicate that most respondents browsed in the mall stores without planning to buy and they are usually in a good mood when they are in the mall. Respondents are attracted to the mall environment (music, decoration, lighting, crowding) and go to malls to relieve boredom, to socialize with friends and because of the convenient location of the malls.